2021
DOI: 10.21203/rs.3.rs-818015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA Profiling Reveals an Abundant ssc-miRNA-148a-3p that Promotes Proliferation and Differentiation during Intramuscular Adipogenesis in Chinese Guizhou Congjiang Pigs Breeds by targeting PPARGC1A

Abstract: BackgroundIntramuscular fat development is regulated by a series of complicated processes, and non-coding RNA (ncRNA) such as microRNA (miRNA) plays a critical role during intramuscular preadipocyte proliferation and differentiation development in pigs. In present research, we detected the expression profiles of miRNA during different differentiation stages, namely, day 0 (D0), day 4 (D4), and day 8 (D8), of intramuscular preadipocytes from the longissimus dorsi muscle of Chinese Guizhou Congjiang pigs to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, peroxisome proliferator-activated receptor-γ coactivator 1α ( PPARGC1A ), which is a key coregulatory transcription factor of mitochondrial function [ 239 , 240 ], is a target of miR-148a [ 241 , 242 ]. Factors responsible for mitochondrial biogenesis and degradation play key roles in the balance of mitochondrial mass in β cells.…”
Section: Mex Mir Signaling and Functional Immaturity Of β Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, peroxisome proliferator-activated receptor-γ coactivator 1α ( PPARGC1A ), which is a key coregulatory transcription factor of mitochondrial function [ 239 , 240 ], is a target of miR-148a [ 241 , 242 ]. Factors responsible for mitochondrial biogenesis and degradation play key roles in the balance of mitochondrial mass in β cells.…”
Section: Mex Mir Signaling and Functional Immaturity Of β Cellsmentioning
confidence: 99%
“…Of importance, ERRγ binds to its coactivator peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α; PPARGC1A ), producing a stable transcription factor ERRγ/PGC-1α complex [ 256 , 257 ]. Intriguingly, both mRNAs of ESRRG and PPARGC1A exhibit highly conserved binding sites for miR-148a [ 242 , 258 ]. As previously mentioned, miR-148a also suppresses PRKAA1 [ 234 ], the catalytic subunit α1 of AMPK, and PRKAG2 [ 235 ], the regulatory subunit γ2 of AMPK.…”
Section: Mex Mir Signaling and Functional Immaturity Of β Cellsmentioning
confidence: 99%
“…Importantly, human and bovine milk fat as well as human and bovine MEX are a rich source of miR-148a (11,101,362,363), which targets key regulatory components of AMPK (225,226,364), thereby attenuating AMPK´s inhibitory function on mTORC1 via AMPK-mediated phosphorylation of TSC2 and Raptor (365,366). Milk fat and MEX miR-148a may stimulate β-cell mTORC1 activity promoting β-cell growth and mass expansion (367).…”
Section: T2dmmentioning
confidence: 99%
“…Ling et al (418) demonstrated that downregulation of PPARGC1A expression in human islets by siRNA, reduced insulin secretion. Remarkably, key signature miRs of milk and MEX including the let-7 family and miR-148a target PPARGC1A (364,419,420) and may thus restrain insulin secretion during the breastfeeding period. Increased plasma levels of miR-148a have been associated with T2DM progression, increased HbA1c, HOMA-IR, and hyperinsulinemia (421) (Table 6).…”
Section: T2dmmentioning
confidence: 99%